2022
DOI: 10.2106/jbjs.22.00573
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative Versus Operative Treatment for Displaced Finger Metacarpal Shaft Fractures

Abstract: Background: Finger metacarpal fractures represent up to 31% of all hand fractures, and most can be treated nonoperatively. Whether operative treatment is superior to nonoperative treatment for oblique and/or spiral finger metacarpal shaft fractures (MSFs) is unknown.Methods: Forty-two patients with displaced oblique and/or spiral finger MSFs were randomized to either nonoperative treatment with unrestricted mobilization or operative treatment with screw fixation. The primary outcome was grip strength in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…However, in a study conducted by Fredrik Peyronson et al in which conservative treatment was compared to operative management in metacarpal fractures, a linear regression analysis showed that the grip strength was better in the dominant hand by 22.2% when compared to the non-dominant side ( p Value = 0.007). [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, in a study conducted by Fredrik Peyronson et al in which conservative treatment was compared to operative management in metacarpal fractures, a linear regression analysis showed that the grip strength was better in the dominant hand by 22.2% when compared to the non-dominant side ( p Value = 0.007). [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge can be critical in decision making and patient counselling. Recent research has shown that non-operative treatment of spiral metacarpal fractures is so good that surgery is rarely going to give a better outcome (Khan and Giddins, 2015; Peyronson et al., 2022). Few patients will choose surgery if advised of that, but a less informed surgeon may recommend surgery meaning any adverse outcomes of that treatment could be a result of their error.…”
Section: Avoidance Of Errorsmentioning
confidence: 99%
“…A group from Uppsala (Sweden) have performed a prospective noninferiority randomized controlled trial to compare nonoperative and operative treatment for displaced finger metacarpal shaft fractures. 8 Overall, 42 patients with oblique or spiral fractures were randomized to screw fixation or nonoperative treatment with unrestricted mobilization. The primary outcome measure was grip strength in the hand, which was injured as compared with the uninjured hand at 12 months’ follow-up.…”
Section: Nonoperative Versus Operative Treatment For Displaced Finger...mentioning
confidence: 99%